Paradigms in Political Science Revisited - Mona Abul-Fadl (International Institute of Islamic Thought, 1989)
It is time for Muslim political scientists to come together to debate the state of the art in their field and to define the grounds and terms for its prospective evolution or transformation in the light of alternative perspectives. The underlying assumptions which provide the parameters and the key concepts which they currently apply in the course of their normal practice should no longer be assumed but should be questioned. To do so, they will need to be made explicit and examined in a new light. The developments of the past decade make this imminent in more than one way. ln the West the souJsearching among social scientists bas intensified and contributed to shaking the profession out of its complacency. The resulting meta-critique has heightened critical awareness. The decade has also coincided with a dawning epistemic consciousness among Muslims. Conscientious scholars and intellectuals have staked their claims to autonomy on the grounds of a critical disaffection with their field. Perceived disjunctures bred that kind of essential tension which prompted a review of foundational dimensions of consciousness and being. They identified their source in dissonant cultural forces and processes comprising education, socialization and the reproduction of knowledge, values, and symbols as underlying the continuities and discontinuities in the fabric of the Ummah. This constituted the diagnosed malaise.' In this process of critical introspection, the idea of the Islamization of knowledge was conceived. Its natural focus was the state of modem knowledge and its modes of diffusion and transmission along the educational and cultural arteries in the Ummah. It contested the myth of modem sciences as value-free, a myth that was particularly dominant within Muslim societies themselves. Claims to valueneutrality were not only questionable as empirical reality, but they were even more dubious and questionable as a moral ideals ...